Quality Improvement through DMAIC: A Case Study of Wire Harness Tape Manufacturing - Buthphorm, Oranicha (Journal of Multidisciplinary in Social Sciences, 2023)
The goals of this research were to identify problems, find solutions and implement DMAIC to improve the high defect rate in the weaving process that was causing high operation cost at a wire harness tape manufacturing in Thailand. In this study, qualitative research was used with samples collected, and the paper gives an insight into the 16-week journey of applying a DMAIC (Define-MeasureAnalyze-Improve-Control) of Six Sigma framework to achieve reducing defects in the weaving process. The study utilized the Six Sigma tools such as brainstorming, SIPOC, affinity diagram, Isikawa diagram, Pareto chart and checklists. As a result, the root cause of significant defects were first, the human problem was defined, human error, no motivation, not enough training. Then an improvement plan was constructed, that included training of SOP, ISO 9001:2015, and CTQs. Next, the problem with machines were defined such as machines were not in the appropriate condition causing them to breakdown and shortages of spare parts to fix the machines. Implementing the preventive maintenance, daily checking, and monthly scheduled maintenance will stop these issues from occurring. Last, the raw material issue, which lacked full inspection, lack of vendor site inspection, and lack of qualified products, the issues can be prevented by implementing a system of value chain management and supplier relationship management with vendor site inspection planning. The ISO 9001:2015 is the significant tool implemented to ensure the company meets quality control and quality assurance. In the end, the desired achievement to reduce 6% to zero defect rate was achieved. The value of this study presents an industrial case that demonstrates how the deployment of Six Sigma and DMAIC can assist manufacturing productivity to achieve quality improvements in their processes.